Shorebird Seasonal Abundance and Habitat-Use Patterns in Punta Rasa, Samborombón Bay, Argentina - Martínez Curci, Natalia Soledad; Isacch, Juan Pablo; Azpiroz, Adrian B. (Waterbirds)
Shorebird assemblage composition and habitat-use patterns were characterized at Punta Rasa during the austral summer, autumn and winter. Compared to other sites within the region, this area showed high species richness, reflected by a total of 22 species recorded within a relatively short time frame. Differences in assemblage structure were driven by the use of estuarine mudflats and oceanic sandy beaches as feeding habitats. During low tide, more species used estuarine environments, achieving the highest total densities. Abundance patterns and assemblage composition also changed seasonally. Maximum total abundance occurred during the austral summer, and minimum total abundance during the austral winter. During the austral summer, the assemblage was dominated by Nearctic migrants such as American Golden-Plover (Pluvialis dominica), Hudsonian Godwit (Limosa haemastica) and White-rumped Sandpiper (Calidris fuscicollis). In addition, Two-banded Plover (Charadrius falklandicus) and American Oystercatcher (Haematopus palliatus) were abundant during the austral autumn. The Red Knot (Calidris canutus), a shorebird that dominated the austral autumn assemblage 25 years ago, was recorded in relatively small numbers during this study, probably reflecting the global population trend of a subspecies of the Red Knot (C. c. rufa) in the past two decades. During the austral winter, resident birds largely dominated the assemblage. However, it is noteworthy that some individuals of nine Nearctic migrant species remained in the area. In the case of the endangered Red Knot, Punta Rasa is, along with Lagoa do Peixe in Brazil, one of the sites in South America with the highest known abundances during the austral winter. Fil: Martínez Curci, Natalia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Isacch, Juan Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. ...